Impact of Public Health Education Program on the Novel Coronavirus Outbreak in the United States - Iboi, Enahoro; Richardson, Ariana; Ruffin, Rachel; Ingram, DeAndrea; Clark, Jailyn; Hawkins, Jala; McKinney, Maati; Horne, Nianza; Ponder, Reyla; Denton, Zoe; Agusto, Folashade B.; Oduro, Bismark; et al. (Frontiers in Public Health, 2021)
The coronavirus outbreak in the United States continues to pose a serious threat to human lives. Public health measures to slow down the spread of the virus involve using a face mask, social-distancing, and frequent hand washing. Since the beginning of the pandemic, there has been a global campaign on the use of non-pharmaceutical interventions (NPIs) to curtail the spread of the virus. However, the number of cases, mortality, and hospitalization continue to rise globally, including in the United States. We developed a mathematical model to assess the impact of a public health education program on the coronavirus outbreak in the United States. Our simulation showed the prospect of an effective public health education program in reducing both the cumulative and daily mortality of the novel coronavirus. Finally, our result suggests the need to obey public health measures as loss of willingness would increase the cumulative and daily mortality in the United States.